Assessment of the Indoor Environment for Education. (June 2019) - Kraus, M; Nováková, P
Abstract: Indoor environment quality (IEQ) and its effect on well-being, productivity and performance are phenomena. Achieving suitable and comfortable indoor environment is a key factor in the creation and operation of the buildings in terms of basic principles of the sustainable development. The poor indoor environment is associated with the Sick Building Syndrome (SBS). The occurrence of pollutants in the indoor environment brings health problems to occupants as well as affects their productivity and performance. The main aim of the contribution is the study of indoor environment for educational purposes. The ordinary university classrooms located on the outskirts of the city České Budějovice (Czechia) are analysed. The classrooms are places, where the students reading, calculating, writing, and solving the assigned tasks. Achieving and satisfying the comfort in the indoor environment for education purposes is necessary for these student's activities. For example, insufficient air exchange and the CO2 concentration above of 1000 ppm, cause fatigue and decreased concentration. The assessment of physical-chemical parameters includes analysis of indoor air temperature [°C], relative humidity [%], Carbon Dioxide (CO2 ) concentration [ppm], and illumination intensity [lx] in the university classrooms. The high-quality sensor for measuring air flow, temperature, humidity, pressure, heat radiation, CO2 concentration and illumination intensity Testo 480 with globe probe, IAQ probe, light probe and comfort level probe is used for measurement. The work is supported by the grant Specific University Research SVV 201802 Address identification and analysis of the determinants of the Indoor Environment Quality (IEQ).